Potential Fraud in The Primary Healthcare - Nizar Fathurrohman; Arlina Dewi (Universitas Muhammadiyah Yogyakarta, 2018)
This study discusses of potential fraud at the primary healthcare. Fraud is more often associated with secondary healthcare, namely hospitals, so that fraud in primary healthcare rarely supervises. Premi of JKN around 38.5 trillion and estimating the potential fraud of around 5% will disappear 1.8 trillion per year. This research used qualitative methods with phenomenological design, as the data are collected using in-depth interview and observation techniques. The number of respondents in this research were 3 public healthcare and 2 private healthcare in X regency. The results showed potential fraud in primary healthcare related to human resources (HR), management of health service, leadership policies, management of capitation funds and operational audits.